An Optimized 4H-SiC Trench MOS Barrier Schottky (TMBS) Rectifier - Ying Wang (IEEE, 2018)
This paper proposes an optimal 4H-silicon carbide trench MOS barrier Schottky (TMBS) Rectifier. The optimal structure of this rectifier is achieved by adding an N− wrapping region at the P+ shielding of the conventional TMBS structure, which significantly reduces the depletion region formed by the P+ shielding region. As a result, the proposed structure provides a lower ON-resistance comparing with the conventional P+ shielding structure. Moreover, we study the electric characteristics of the proposed structure via numerical simulation. Such a structure improves the specific ON-resistance and figure of merit of the conventional P+ shielding TMBS by 32.2% and 48.4%, respectively, and offers a high breakdown voltage, i.e., up to 1908 V.